h/4=9=11

Simple and best practice solution for h/4=9=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h/4=9=11 equation:



h/4=9=11
We move all terms to the left:
h/4-(9)=0
We multiply all the terms by the denominator
h-9*4=0
We add all the numbers together, and all the variables
h-36=0
We move all terms containing h to the left, all other terms to the right
h=36

See similar equations:

| 8t-39=6t | | 4(x+2)-5=3 | | 49.96-0.13x=55.96-0.08x | | 35-4m=7m-2 | | 0=−2x+3 | | (10.01)x+(11.01)(1-x)=10.81 | | 8x—3=7x—1 | | 4/9x+8=-4 | | 3+x/5=5 | | -5y+19=-4y | | -6z-8=3z+19 | | 20t+15=19t | | (0)=−2x+3 | | 11c-48=8c | | 5-3x=-9x+17 | | C=2+3.14(•r) | | 8x+12=12x+4.8 | | -7+13n=12n+11 | | 6(1/2x+1/3)=3(x+4) | | 3t+43=6t-17 | | 38-6v=-(5v+8) | | 6x-9=3x-5+7 | | -8-4p=-16 | | -78=4x*26 | | n3=-20 | | -(9n-5)=-10+10(n-8) | | -2(1-x)+x=2x-7 | | -4t=20-8t | | 2x-(x-2)=x+32=3 | | 4-3d=+8 | | 3w-9=33.21 | | -(9n-5)=-10+10(n-80 |

Equations solver categories